Retrospective audit of inter-fraction motion for pelvic node radiotherapy in prostate cancer patients. Issue 2 (May 2021) - Lawes, R.; Carter, E.; Hussein, M.; Murray, J.; McNair, H.A.
Abstract: Introduction: Pelvic lymph nodes move independently to the prostate. When delivering radiotherapy to prostate and pelvic lymph nodes, daily inter- and intra-fraction anatomical changes need to be accounted for. Planning target volume (PTV) margins, grown from the pelvic lymph node clinical target volume need to be determined, to account for this variation in position. Methods: Twenty patients who had daily online image guided radiotherapy to prostate and pelvic lymph nodes between April and December 2018 were selected. Ten pre-treatment verification images using cone beam CT from each patient were registered to pelvic bone anatomy, prostate soft tissue or fiducial markers and pelvic lymph node soft tissue to assess the accuracy of treatment delivery. Population systematic and random errors and PTV margins were calculated. Results: PTV margins of 0.4 cm, 0.4 cm and 0.7 cm left–right (LR), superior–inferior (SI) and anterior–posterior (AP) respectively were derived for the pelvic lymph nodes when registering to prostate. PTV margins of 0.3 cm, 0.2 cm and 0.4 cm LR, SI and AP respectively were derived for the pelvic lymph nodes when registering to bone. There was a posterior systematic shift of the prostate during the treatment course. Conclusion: There is differential motion of pelvic lymph nodes to prostate and in the era of prostate and pelvic radiotherapy for patients with node positive prostate cancer; there is increasing importance in the accuracy of dose delivery to the involved lymph node. Hence, this group of patients may benefit from personalised radiotherapy PTV margins, especially if the involved pelvic lymph node is within the anterior part of the clinical target volume. Implications for practice: Optimisation of dose delivery to the pelvic lymph nodes when prioritising the prostate in prostate and pelvic lymph node image guided radiotherapy.